2015 Workshop on Modeling and Simulation of Cyber-Physical Energy Systems (MSCPES) 2015
DOI: 10.1109/mscpes.2015.7115399
|View full text |Cite
|
Sign up to set email alerts
|

Estimating state of charge and state of health of rechargable batteries on a per-cell basis

Abstract: Much of current research on State-of-Charge (SOC) and State-of-Health (SOH) tracking for rechargeable batteries such as Li-ion focuses primarily on analyzing single cells, or otherwise treat a set of series-connected cells as a homogeneous unit. Since no two cells have precisely the same properties, for applications involving large batteries this can severely limit the accuracy and utility of the approach. In this paper we develop an model-driven approach using a Dual Unscented Kalman Filter to allow a Battery… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…From our investigation on related work (presented in Section V.C), we could not find any FPGA-based embedded hardware architectures, specifically for PB-MPC. Our investigation further revealed that most of the existing works [10], [11], [12], [13] on EKF for batteries, were based on the ECM approach for estimating the state of charge (SOC) and state of health (SOH) of the batteries, and not much research has been done on physics-based (PB) EKF. Existing works in the published literature for PB-MPC designs, such as [7], [9], [15] were focused mainly on using Matlab software models to verify and improve the physics-based (PB) approaches.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…From our investigation on related work (presented in Section V.C), we could not find any FPGA-based embedded hardware architectures, specifically for PB-MPC. Our investigation further revealed that most of the existing works [10], [11], [12], [13] on EKF for batteries, were based on the ECM approach for estimating the state of charge (SOC) and state of health (SOH) of the batteries, and not much research has been done on physics-based (PB) EKF. Existing works in the published literature for PB-MPC designs, such as [7], [9], [15] were focused mainly on using Matlab software models to verify and improve the physics-based (PB) approaches.…”
Section: Introductionmentioning
confidence: 89%
“…The effectiveness of the MPC algorithm depends on the accuracy of the mathematical model of the battery cell. Two main mathematical models of the battery cell are the equivalent circuit model (ECM) [10], [11], [12], [13] and the electro-chemical physics-based model (PBM) [4], [7]. The ECM model comprises simplified algorithms and provides solid performance.…”
Section: Introductionmentioning
confidence: 99%
“…A similar example appears in [95,81] which is concerned with assessing the state of health (e.g. degree of degradation from nominal capacity) of rechargeable cells.…”
Section: Multiple Kalman Filtersmentioning
confidence: 99%
“…The following section details an extended case study on piecewise-affine Kalman Filtering for tracking cell voltages in large batteries. It is based on results appearing in [80] and [81].…”
Section: Battery Monitoringmentioning
confidence: 99%
See 1 more Smart Citation